Microstructural modulation of TiAl alloys for controlling ultra-precision machinability. (March 2022) - Zhang, Yu; Lee, Yan Jin; Chang, Shuai; Chen, Yuyong; Bai, Yuchao; Zhang, Jiong; Wang, Hao
Abstract: TiAl intermetallic alloys have attracted considerable attention in aerospace applications over the last few decades owing to their low density and superior mechanical properties at high temperatures. However, these alloys are also known as difficult-to-machine materials that hinder efficient manufacturing. This study presents a systematic investigation on the machinability of TiAl alloys with three types of microstructures obtained by different heat treatment parameters. These were classified as near-gamma (NG), duplex (DP), and fully lamellar (FL). The machinability was evaluated based on the cutting forces and machined surface roughness. The material with α2 /γ lamellar structures (FL) exhibited the lowest cutting force (3.21 N). However, produced a rougher surface (80 nm Ra) as compared to the NG microstructure (4.69 N and 47 nm Ra). Electron backscattering diffraction (EBSD) evaluation of the primary deformation zone in the cutting chips revealed that insufficient heat energy was converted from plastic deformation for recrystallization or β+γ→α2 phase transformation to occur. This indicated that the deformation mechanisms were significantly dependent upon the plasticity. The NG microstructure demonstrated a higher degree of plasticity in the primary deformation zone, which was attributed to the combined effect of super-dislocation decomposition, ordinary dislocation slip, and refined mechanical twins with preferred orientation along the < 11 2 ¯ > 111 crystallographic orientation. Conversely, the FL microstructure exhibited brittleness during chip formation due to the weak bonding force between hexagonal α2 and tetragonal γ phases that led to preferential micro-cracking along each interface. Reducing the crystal orientation is conductive for improving machined surface quality. The notion of enhanced brittleness to explain the reduction in cutting forces due to the dissipation of energy through fracture was supported with numerical simulations. Microscopic evaluation was used to understand the deformation differences of the equiaxed γ grain and α2 /γ lamellar microstructure during micro-cutting. Additionally, enhanced the understanding of the deformation mechanism of these multi-phase alloys. Graphical abstract: Image 1 Highlights: Ultra-precision machinability of various TiAl microstructures is investigated. Increasing α2 /γ lamellae content increases hardness but reduces cutting forces. Refined mechanical twins can enhance the strength without loss in ductility. Low crystal orientation is conducive for improving machined surface quality.